Forecasting of the Income Tax in the Slovak Republic - Pavlik, Martin (Prognozowanie podatku dochodowego w Republice Słowackiej, 2011)
The author focuses on forecasting income tax in cases where the time series is short. He uses the methodology which was described in his previous papers and applied on the monthly basis. He applies the methodology on an annual quarterly basis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 125-131
Keywords: podatek dochodowy; prognozowanie; income tax; forecasting